Building real-‐time web application based on Google Web Toolkit (GWT) and HTML5 - Soh, Teck Yu. (2011)
This research report will provide people with an insight on how a web application (AskandHelp.me) can be optimized to work in real-time environment and with large number of concurrent users, by using Google Web Toolkit (GWT) as the main development tool, and JavaScript Object Notation (JSON), which is used as the data exchange format between the client and server. On top of that, with the implementation of HTML5 Canvas and Web SQL Storage as part of the main features in the web application, how it can help to enhance the overall experience for the users, by having more interactivity and a browser plug-in free environment. AskandHelp.me is basically a real-time web application, which is based on Q&A Methodology, whereby people can ask and answer questions. In addition, they can even make use of the feature called Sketch Pad (implemented with HTML5 Canvas), to sketch anything they want, and attach it to the questions. And if they like the answers to their questions, they can even choose to add them to the favourites.